2020
DOI: 10.1590/1983-21252020v33n218rc
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Regime on Fine Root Growth in a Seasonally Dry Tropical Forest

Abstract: ABSTRACT Seasonally dry tropical forests (SDTF) usually present dry seasons of eight or more months. Considering the concerns about the resilience of SDTF to climate changes, the objective of this study was to evaluate the effect of the rainfall regime on fine root growth in a SDTF. The experiment started at the end of the wet season (July 2015), when fine roots were evaluated and ingrowth cores were implemented. The temporal growth of fine roots in the 0-30 cm soil layer was monitored, considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…These lower values can be explained by the degree of degradation in the area, as with the reduction of vegetation coverage, the amounts of roots also decreased (Premrov et al, 2017). According to Andrade et al, (2020), the amount of fine roots in pasture area ranged from 5.33 to 25.83 g, which are within values found in this study. The same authors Research, Society andDevelopment, v. 11, n. 1, e53811125333, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i1.25333 6 also reported that the results found in their work in relation to the behavior of fine root biomass are inversely proportional to depth, and the amounts of roots decreased around 36% in the layer of 5-30 cm.…”
Section: Resultssupporting
confidence: 80%
“…These lower values can be explained by the degree of degradation in the area, as with the reduction of vegetation coverage, the amounts of roots also decreased (Premrov et al, 2017). According to Andrade et al, (2020), the amount of fine roots in pasture area ranged from 5.33 to 25.83 g, which are within values found in this study. The same authors Research, Society andDevelopment, v. 11, n. 1, e53811125333, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i1.25333 6 also reported that the results found in their work in relation to the behavior of fine root biomass are inversely proportional to depth, and the amounts of roots decreased around 36% in the layer of 5-30 cm.…”
Section: Resultssupporting
confidence: 80%
“…Recent studies on DH species found that root biomass was largely concentrated near the tree base and within the top 20 to 40 cm of soil (Albuquerque et al., 2015 ; Costa et al., 2014 ). The growth of fine roots is driven by water availability, which explains why there is high investment in root length per unit of biomass in surface soils (Andrade et al., 2020 )—roots must maximize lateral exploitation of soil water, especially in dry or shallow soils. Thus, we argue that the extent to which DH trees exploit deeper soil water sources is limited, and instead, they on lateral versus vertical soil water exploitation.…”
Section: Discussionmentioning
confidence: 99%
“…For all vegetation scenarios (potential, contemporary, and future) except those above 60°N (described below), we estimated biome‐specific rooting depths by assigning rooting depth functions derived from empirical data compiled in the Fine Root Ecology Database (FRED) and the National Ecological Observatory Network (NEON) database (Iversen et al., 2021; NEON, 2021). These data sets have recently expanded rooting depth knowledge beyond earlier works (e.g., Jackson et al., 1996; Schenk & Jackson, 2005; Zeng, 2001) by accumulating new datapoints detailing root trait and distribution patterns in diverse biomes (Andrade et al., 2020; Krasowski et al., 2018; Lozanova et al., 2019; Montagnoli et al., 2018). However, to date no one has harmonized and analyzed these data sets to produce equations describing global rooting depth distributions.…”
Section: Methodsmentioning
confidence: 99%